Опорно-рухова система : методичні рекомендації для самостійної роботи студентів біологічного факультету 1-го року навчання з дисципліни «Анатомія та гістологія людини» спеціальності: 014.05 Середня освіта (Біологія та здоров’я людини) [Електронний ресурс] - Шерстюк, Сергій Олексійович; Наконечна, Світлана Анатоліївна (Харків : Харківський національий університет імені В.Н. Каразіна, 2024)
Методичні рекомендації (електронний ресурс) для студентів з дисципліни «Анатомія та гістологія людини» розроблені у відповідності з діючими програмами з анатомії та гістології людини для студентів вищих навчальних закладів освіти. Посібник призначений для роботи студентів під час підготовки до занять з курсу «Біологія та здоров´я людини». До кожної теми наведені перелік практичних навичок та контрольних питань. Теми проілюстровані рисунками та схемами, які полегшують сприйняття матеріалу та сприяють його кращому засвоєнню. Матеріали дають змогу сформувати у студентів правильне розуміння закономірностей будови організму людини. Для студентів біологічного факультету.

Methodical recommendations (electronic resource) for students of the discipline "Human anatomy and histology" are developed in accordance with the current programs on human anatomy and histology for students of higher educational institutions. The manual is intended for students' work during preparation for classes in the course "Biology and human health". Each topic includes a list of practical skills and control questions. The topics are illustrated with pictures and diagrams, which facilitate the perception of the material and contribute to its better assimilation. The materials make it possible for students to form a correct understanding of the laws of the structure of the human body. For students of the Faculty of Biology.
Musculoskeletal system: methodological recommendations for the independent work of students of the Faculty of Biology of the 1st year of study in the discipline "Human Anatomy and Histology", specialty: 014.05 Secondary Education (Biology and Human Health) [Electronic resource]
Keywords: MEDICINE::Morphology::Anatomy; вісі та площини людського тіла; скелет голови; скелет верхньої кінцівки; скелет нижньої кінцівки; перелік практичних навичок; з’єднання кісток скелета; з’єднання кісток черепа; з’єднання кісток тулуба; з’єднання кісток верхньої кінцівки; з’єднання кісток нижньої кінцівки; розміри таза; міологія; м’яз як орган; м’язи голови; м’язи шиї; трикутники шиї; м’язи спини; м’язи грудної клітки; м’язи живота; фасції і топографія живота; пахвинний канал; м’язи верхньої кінцівки; м’язи нижньої кінцівки; перелік практичних навичок; axes and planes of the human body; skeleton of the head; skeleton of the human body; skeleton of the upper limb; skeleton of the lower limb; list of practical skills; connection of the bones of the skeleton; connection of the bones of the skull; connection of the bones of the trunk; connection of the bones of the upper limb; connection of the bones of the lower limb; the dimensions of the pelvis; myology; muscle as an organ; muscles of the head; muscles of the neck; triangles of the neck; muscles of the back; muscles of the chest; muscles of the abdomen; fascia and topography of the abdomen; inguinal canal; muscles of the upper limb; muscle muscles of the lower limb; a list of practical skills